Taking to the Streets in the Shadow of Austerity: A Chronology of the Cycle of Protests In Spain, 2007-2015 - Martín Portos (Partecipazione e Conflitto, 2016)
Based on theories of cycles of collective behavior, this piece establishes a periodization of the cycle of anti-austerity and anti-political status quo protests in the shadow of the Great Recession that Spain faced between 2007 and 2015. More specifically, it tries to explain why the peak of protests persisted for so long: radicalization was contained, institutionalization postponed and protesters’ divisions avoided. The crucial argument here, an innovation with regards to the classic theories of cycles, is that the high standards of mobilization persisted for a long time as the result of the issue specialization of a more gen-eral anti-austerity fight and the strategic alliances ––with varying degrees of formality–– that new civil organizations forged with the unions. For illustrating the longitudinal dynamics of the cycle of protests, we use original protest event data